The Effect of Public Subsidies on Library Services - Sunaga, Kazuyuki (Qualitative and Quantitative Methods in Libraries; Vol 7 No 4 (2018): December 2018 Issue, 2019)
This research aims to clarify whether government subsidies have financial influence on public library services in the area adjacent to the US military facilities in Japan. Japan’s Ministry of Defense has provided subsidies to areas adjacent to US military facilities. Part of subsidies from the Ministry of Defense of Japan are allocated as the operating costs of public libraries. In this research, we focus on the case studies of Eniwa City in Hokkaido. We consider the influence and problems on the communities, the facilities and services of the public libraries from the proportion of subsidies of the Ministry of Defense to the educational expenses of each local government